Life path and the main directions of scientific activity of O.P. Sannikova - Kuznetsova, Oksana; Orishchenko, Oksana; Chernozhuk, Yuriy (Psyhology & society, 2019)
Life path and the main directions of scientific activity of O.P. Sannikova